Predator‐scale spatial analysis of intra‐patch prey distribution reveals the energetic drivers of rorqual whale super‐group formation. (9th February 2021) - Cade, David E.; Seakamela, S. Mduduzi; Findlay, Ken P.; Fukunaga, Julie; Kahane‐Rapport, Shirel R.; Warren, Joseph D.; Calambokidis, John; Fahlbusch, James A.; Friedlaender, Ari S.; Hazen, Elliott L.; Kotze, Deon; McCue, Steven; et al.
Abstract: Animals are distributed relative to the resources they rely upon, often scaling in abundance relative to available resources. Yet, in heterogeneously distributed environments, describing resource availability at relevant spatial scales remains a challenge in ecology, inhibiting understanding of predator distribution and foraging decisions. We investigated the foraging behaviour of two species of rorqual whales within spatially limited and numerically extraordinary super‐aggregations in two oceans. We additionally described the lognormal distribution of prey data at species‐specific spatial scales that matched the predator's unique lunge‐feeding strategy. Here we show that both humpback whales off South Africa's west coast and blue whales off the US west coast perform more lunges per unit time within these aggregations than when foraging individually, and that the biomass within gulp‐sized parcels was on average higher and more tightly distributed within super‐group‐associated prey patches, facilitating greater energy intake per feeding event as well as increased feeding rates. Prey analysis at predator‐specific spatial scales revealed a stronger association of super‐groups with patches containing relatively high geometric mean biomass and low geometric standard deviations than with arithmetic mean biomass, suggesting that the foraging decisions of rorqual whales may be more influenced by the distribution of high‐biomass portions of a patch than total biomass. The hierarchical distribution of prey in spatially restricted, temporally transient, super‐group‐associated patches demonstrated high biomass and less variable distributions that facilitated what are likely near‐minimum intervals between feeding events. Combining increased biomass with increased foraging rates implied that overall intake rates of whales foraging within super‐groups were approximately double those of whales foraging in other environments. Locating large, high‐quality prey patches via the detection of aggregation hotspots may be an important aspect of rorqual whale foraging, one that may have been suppressed when population sizes were anthropogenically reduced in the 20th century to critical lows. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.